2020
DOI: 10.3390/ijerph17062079
|View full text |Cite
|
Sign up to set email alerts
|

Human Enteric Pathogens in Eight Rivers Used as Rural Household Drinking Water Sources in the Northern Region of South Africa

Abstract: People living in rural areas still rely on the use of environmental water that is contaminated by human and animal activities. This study assessed the occurrence of human enteric pathogens in rivers that are used by rural communities Vhembe District of South Africa as a source of drinking water covering two seasons (winter and summer) over a one-year period. Water quality was assessed using physico characteristics and indicator organisms (total coliforms, E. coli, Clostridium perfringens). Pathogens tested inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 76 publications
1
19
1
Order By: Relevance
“… Poor sanitation and hygiene : Unhygienic practices such as open defaecation, and the use of unimproved and poorly designed on-site sanitation systems such as pit latrines, bucket latrines and septic tanks are common. In most informal settlements such as slums, squatter camps and refugee camps, on-site sanitation systems may be closely juxtaposed with vulnerable drinking water sources such as wetlands, and surface and shallow groundwater systems ( Potgieter et al, 2020 ). This is because, in such settings, the landholding per household is very small, leading to overcrowding.…”
Section: Significance Of the Covid-19 Faecal-oral Hypothesis In Develmentioning
confidence: 99%
See 1 more Smart Citation
“… Poor sanitation and hygiene : Unhygienic practices such as open defaecation, and the use of unimproved and poorly designed on-site sanitation systems such as pit latrines, bucket latrines and septic tanks are common. In most informal settlements such as slums, squatter camps and refugee camps, on-site sanitation systems may be closely juxtaposed with vulnerable drinking water sources such as wetlands, and surface and shallow groundwater systems ( Potgieter et al, 2020 ). This is because, in such settings, the landholding per household is very small, leading to overcrowding.…”
Section: Significance Of the Covid-19 Faecal-oral Hypothesis In Develmentioning
confidence: 99%
“…Such research should also target and prioritize areas associated with putative faecal contamination such as informal settlements including slums, squatter camps and refugee camps. Communities in such informal settlements often rely on untreated raw water abstracted from shared and unsafe drinking water sources, which are often closely juxtaposed with on-site sanitation systems ( Pujari et al, 2012 : Potgieter et al, 2020 ). Developing countries with recurrent outbreaks of human infections transmitted via the faecal-oral route such as cholera and typhoid could constitute the ideal settings or ‘ worst-case scenario ’ to investigate the faecal-oral hypothesis.…”
Section: Significance Of the Covid-19 Faecal-oral Hypothesis In Develmentioning
confidence: 99%
“…that seem unlikely to provide convincing results (e.g., sample volumes as low as 10 ml, with minimal processing steps, and mZn for detection of oocysts). Nevertheless, it is these articles that often provide data indicating the highest proportion of samples considered positive (over 40%), while papers using standardized methods for water analysis (those of ISO or US Environmental Protection Agency) tend to report lower proportions of positive samples [e.g., the work of Morris et al from Kenya (83), Kifleyohannes and Robertson from Ethiopia (84), or Potgjeter et al from South Africa (85)]. This suggests that the lack of specific detection techniques used in other studies may have resulted in false positive results.…”
Section: Water As a Cryptosporidium Transmission Vehicle In Africa Anmentioning
confidence: 99%
“…The indicator E. coli counts were used as the norm to indicate the effectivity of the point-of-use PFP filter, and Table 1 showed that the filters removed the indicator bacteria from the borehole water. However, the average filter performance of the Ghana ceramic pot filters did not meet the recommended 2 log10 reduction for home treatment [ 172 ]. The PFP ceramic filters are manufactured in different low-income countries, and although the design is the same, the manufacturing processes and the materials used have an impact on the efficacy of the filters [ 172 , 173 , 174 ].…”
Section: Discussionmentioning
confidence: 99%